Pancreatic Cancer Cell Lines Can Induce Prostaglandin E2 Production from Human Blood Mononuclear Cells. (12th July 2011) - Grekova, Svitlana P.; Angelova, Assia; Daeffler, Laurent; Raykov, Zahari
Abstract : Accumulating evidence suggests an important role for cyclooxygenase-2 (COX-2) in the pathogenesis of a wide range of malignancies. The protumorigenic properties of COX-2 are generally thought to be mediated by its product, PGE2, which is shown to promote tumor spread and growth by multiple mechanisms but most importantly through modulation of the local immune response in the tumor. Pancreatic tumor cells produce various amounts of PGE2, some of them being even deficient in COX enzymes or other PGE2 synthases. Here we describe that, beside pancreatic tumor cells or stromal fibroblasts, human peripheral blood mononuclear cells can also produce PGE2 upon coculture with pancreatic cancer cells. Stimulating of cellular cPLA2 within PBMCs by secreted factors, presumably sPLA2, from tumor cells appeared crucial, while the direct contact between PBMCs and PDACs seemed to be dispensable for this effect. Our data is emphasizing the complex interactions participating in the formation of the tolerogenic immune milieu within pancreatic tumors.